어머니의 신체접촉 변화에 대한 영아 반응의 민감성 - 곽금주(Keum Joo Kwak); 김수정(Su Chung Kim); 정윤경(Yoon Kyung Jeong) (Korean Journal of child studies, 2005)
The present study examined the effectiveness and communications functions of mothers' touch on the responses of their 6-month-old infants using the Still-Face (SF) situation. Participants were 67 infant-mother dyads from Seoul and Gyeonggi province. Positive and negative responses of infants were measured by SF interactions and by three different touch conditions. Touch types were measured by a coding scheme based on Suchung Kim and Keumjoo Kwak (2003; 2(04). Results showed that mothers' touch affected baby's responses by increasing positive responses and decreasing negative responses. The positive and negative responses of infants differed by the three different touch conditions, indicating that mothers use different touch types according to touch conditions; these variations in touch function as an important channel of communications.